Sex Gratification in Indonesian Anti-Corruption Law: What is the Problem? - Yustikarini, Hesty Dian (Law Research Review Quarterly, 2021)
The phenomenon of prostitution in Indonesia has become a negative specter that refers to its dilapidated moral society. This polemic is one of several different dimensions. Stewardship is also felt because law enforcement is not entirely. Prostitution is a name given to indicate the act in which a woman sends herself to relate to the opposite sex in need of money or other forms of payment. Inspired by the rampant sexual gratification cases among state officials. Ratification process and goods but sadness gratification in expanding sexual section. Added the sexy offender (female) underage. Previously gratification is already in Law Number 20 the Year 2001 on Corruption Eradication in article 12 B, but not yet directly in the scope of sex gratification. Thus there needs to be a legal reform synchronized with the rules and protection of human rights for working women. Until now the sexy gratification case is still taboo because it is considered apathetically State has not been possible to do and provide a deterrent effect for service providers, separation and distribution for the perpetrators of sexual. This is the polemic that must be emphasized from the rising.